Curing of large cardamom (Amomum subulatum Roxb.) : Fabrication of a new dryer and a comparative study of its performance with existing dryers - M L SHANKARANARAYANA, JOHNY JOSEPH, B RAGHAVAN, G NANJUNDAIAH, (Journal of Spices and Aromatic Crops, 1996)
A simple natural convection dryer that could be easily dismantled and transported was designed, fabricated and field tested in a large cardamom (Amomum subulatum) plantation in Sikkim, India. The thermal efficiency of the dryer (5.2%).was much higher compared to the traditional curing house dryer (1.8%) thus saving substantial fuel. The dryer had a capacity of 300 kg of fresh cardamom capsules which was adequate for most ofthe plantations in the region. The time taken for drying the fresh capsules to a moisture content of about 10% was 24 h which was much less compared to conventional bhatti drying (55 h) and curing house drying (42 h). The quality of the dried product with respect to flavour and colour was also superior to that obtained from the other two methods of drying.